Converts in the Dead Sea Scrolls, The Gēr and Mutable Ethnicity. - Carmen Palmer (Studies on the Texts of the Desert of Judah, 2018)
Converts in the Dead Sea Scrolls examines the meaning of the term gēr in the Dead Sea Scrolls. While often interpreted as a resident alien, this study of the term as it is employed within scriptural rewriting in the Dead Sea Scrolls concludes that the gēr is a Gentile convert to Judaism. Contrasting the gēr in the Dead Sea Scrolls against scriptural predecessors, Carmen Palmer finds that a conversion is possible by means of mutable ethnicity. Furthermore, mutable features of ethnicity in the sectarian movement affiliated with the Dead Sea Scrolls include shared kinship, connection to land, and common culture in the practice of circumcision. The sectarian movement is not as closed toward Gentiles as has been commonly considered.